PENGARUH KEMATANGAN EMOSI TERHADAP SIKAP TASAMUH SANTRI PONDOK PESANTREN SABILURROSYAD KOTA MALANG - Muhammad Zainurroziqin; Rosichin Mansur; Lia Nur Atiqoh Bela Dina (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Intolerant attitude is the beginning of division. Intolerance will spread easily if someone does not have good emotional maturity. A little provocation, division will explode. With the emotional maturity possessed, a person is also expected to have a tasamuh’s attitude that is useful for overcoming this intolerant attitude. This study aims to describe how the emotional maturity, attitude of the students of Islamic Boarding School Sabilurrosyad Malang, and the influence of emotional maturity and attitude of the Islamic students of Islamic Boarding School Sabilurrosyad Malang. The approach used is a quantitative approach. Data collection techniques with questionnaire, documentation and observation methods. While testing the hypothesis using simple linear regression analysis. The results of this study indicate that the emotional maturity of students is 52.5% (moderate), the attitude of tasamuh is 53.75% (high), and shows the influence of emotional maturity on the Tasamuh’s attitude of students in Islamic Boarding School Sabilurrosyad Malang.